2020
DOI: 10.21203/rs.3.rs-70798/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Modified Method to Treat Severe Asymptomatic Pre-existing Degeneration of Adjacent Segment: A Retrospective Case-Control Study

Abstract: Background: Pre-existing degeneration of adjacent segment is an important risk factor for adjacent segment degeneration (ASD), but limited and controversial studies have addressed its management.Methods: Patients with symptomatic degeneration of the L5/S1 segment warranting surgical interference and severe asymptomatic degeneration of the L4/5 segment were retrospectively analyzed. Among them, those who underwent interbody fusion in the causative (L5/S1) segment and distraction of the intervertebral space and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These previous studies have helped us to better understand and prevent ASD. However, defining the surgical strategy in patients with lumbar spondylolisthesis and preoperative degeneration at the adjacent segment is difficult and several techniques had been reported: Zhang et al 14 performed a lumbar interbody fusion in the spondylolythetic segment, followed by bisegmental placement of a pedicle screw rod system, which was used to distract the adjacent segment. Then, facet fusion in this segment was performed by V-spahed osteotomies which were filled with bone.. Kim et al 15 found that an interspinous device at the cephalad adjacent degenerative segment could reduce the loss of disk height and alleviates postoperative low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…These previous studies have helped us to better understand and prevent ASD. However, defining the surgical strategy in patients with lumbar spondylolisthesis and preoperative degeneration at the adjacent segment is difficult and several techniques had been reported: Zhang et al 14 performed a lumbar interbody fusion in the spondylolythetic segment, followed by bisegmental placement of a pedicle screw rod system, which was used to distract the adjacent segment. Then, facet fusion in this segment was performed by V-spahed osteotomies which were filled with bone.. Kim et al 15 found that an interspinous device at the cephalad adjacent degenerative segment could reduce the loss of disk height and alleviates postoperative low back pain.…”
Section: Discussionmentioning
confidence: 99%